2017
DOI: 10.1002/tea.21413
|View full text |Cite
|
Sign up to set email alerts
|

Gender, complexity, and science for all: Systemizing and its impact on motivation to learn science for different science subjects

Abstract: The present study is based on a large cross‐cultural study, which showed that a systemizing cognition type has a high impact on motivation to learn science, while the impact of gender is only indirect thorough systemizing. The present study uses the same structural equation model as in the cross‐cultural study and separately tests it for physics, chemistry, and biology. The model was confirmed for physics and chemistry, but not for biology. This is interpreted as empirical evidence for a cognitive difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 90 publications
2
27
0
4
Order By: Relevance
“…These were formed as constructs assembled from general opinions on a discipline (subjG), its school content (subjES, subjSS), and classroom experiences (subjTES, subjTSS). Our tentative assumption was that the STEM subjects Biology, Chemistry, Physics, Mathematics, Technics and Technology, and Informatics are entities, each with its body of knowledge taught as part of varied teaching cultures and practices (Zeyer, ). Therefore, we did not take them as an amalgam but instead formed second‐order variables as a construct of opinion about the content and classroom experiences at different school levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were formed as constructs assembled from general opinions on a discipline (subjG), its school content (subjES, subjSS), and classroom experiences (subjTES, subjTSS). Our tentative assumption was that the STEM subjects Biology, Chemistry, Physics, Mathematics, Technics and Technology, and Informatics are entities, each with its body of knowledge taught as part of varied teaching cultures and practices (Zeyer, ). Therefore, we did not take them as an amalgam but instead formed second‐order variables as a construct of opinion about the content and classroom experiences at different school levels.…”
Section: Methodsmentioning
confidence: 99%
“…The factors can be broadly classified as gender, personality, structural variables, and curriculum variables (Trumper, ), the last of which falls within the scope of the present study. Because of the general scope of the study, with its orientation toward content and classroom experiences in STEM subjects, we did not test our models separately by gender (Baram‐Tsabari & Yarden, ; Fredricks, Hofkens, Wang, Mortenson, & Scott, ; Zeyer, ) or any other personal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, research has shown that the lack of addressing empathic cognition in science classrooms contributes to low motivation among many students, particularly females (e.g., Zeyer, 2017). Therefore, it has been suggested that there are benefits from the intrinsic involvement of the human factor in S|E|H issues in order to 'include empathy more seriously and consistently, but with due caution, in science learning' (Zeyer & Dillon, 2019, p. 297).…”
Section: The Role Of Empathy In Complex Science|environment|health Comentioning
confidence: 99%
“…Mit Zeyer (2017) wurde für den naturwissenschaftlichen Bereich davon ausgegangen, dass dieser Unterricht im Sinne der "Science for the best systemizers" ist, weil er im Sinne der beschriebenen "predictional control" (vgl. Baron-Cohen et al, 2003) danach vorgeht, zu vorgegebenen Experimenten Vermutungen aufzustellen und diese zu prüfen.…”
Section: Ableitung Von Möglichkeiten Einer Motivationsfördernden Empaunclassified
“…Wie in Kapitel 2.2.4 dargelegt, wird inzwischen eher Abstand von der Berechnung des Brain Types genommen, da nur die Höhe des SQ-Wertes für die Motivation, sich mit Naturwissenschaften zu beschäftigen, ausschlaggebend sein soll(vgl. Svedholm-Häkkinen & Lindeman, 2016;Zeyer, 2017). Um die in dieser Studie erreichten Werte aber mit den in der Literatur angegebenen vergleichen zu können, wurden die Brain Types der getesteten Kinder ermittelt.…”
unclassified